El reto actual del control de los viajeros frente a la COVID-19 - Santos León, Mirta; Mirabal Requena, Juan Carlos; Álvarez Escobar, Belkis (Mediciego, 2020)
As a necessary biosecurity measure, Cuba closed its borders since March 24, 2020 and only some flights of a humanitarian and commercial nature were allowed.